Biobased liquid crystalline poly(coumarate)s composites and their potential applications. (December 2020) - Singh, Maninder; Takada, Kenji; Kaneko, Tatsuo
Abstract: Poly(coumarate)s has been widely recognised as biobased liquid crystalline polymers and their monomers are used for developing photoreactive materials. In addition, the monomers are synthesized via shikimate pathway in plants and bacteria. Further, these monomers are used as precursors for developing polyesters with enhanced mechanical properties. The biobased monomers such as p-hydroxy cinnamic acid (4HCA), ferulic acid (MHCA) and dihydroxycinnamic acid (DHCA) are used to develop thermotropic liquid crystalline polymers via polycondensation. In this report, various biobased liquid crystalline polymers, their properties and liquid crystalline biohybrids are reviewed. Highlights: Biobased liquid crystalline (LC) polymers are briefly reviewed. Synthesis of LC homo and co-polymers from the 'Phytomonomers' are reviewed. Thermal and mechanical properties of the polymers based on the LC properties are discussed. Future research direction of LC based polymers and their composites are prospected.